Trend Bisnis Digital UMKM Hampers dan Gift Mooi Bucket : Implementasi Strategi Pemasaran Digital Pendampingan Kewirausahaan di Kota Malang - Dyah Ayu Dwi Kusumaingrum; Indah Adawiyyah; Agus Hermawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Digital business transformation has become one of the main necessities for Micro, Small, and Medium Enterprises (MSMEs) to compete in the modern era. This research discusses implementing digital marketing strategies through an entrepreneurship mentoring program for Mooi Gift MSMEs, which focuses on hampers and gift products in Malang. The methods used include individual approaches, training, and rebranding, to improve operational efficiency, digitalizing bookkeeping, and optimizing digital marketing. The mentoring results include the creation of e-commerce accounts, social media rebranding, digital financial management training, and website development to expand market reach. The findings indicate that digital marketing strategies can enhance SMEs' visibility and competitiveness while positively impacting product sales and branding. This study recommends continuously monitoring and developing digital marketing strategies so MSMEs can constantly adapt to market dynamics.